CLDN6 triggers NRF2-mediated ferroptosis through recruiting DLG1/PBK complex in breast cancer - Da Qi; Yan Lu; Huinan Qu; Yuan Dong; Qiu Jin; Minghao Sun; Chengshi Quan (Cell Death and Disease, 2025)
Abstract We previously identified CLDN6 as a pivotal tumor suppressor in breast cancer and unexpectedly discovered that overexpression of CLDN6 resulted in characteristic ultrastructural alterations of ferroptosis. However, the exact mechanism by which CLDN6 triggers ferroptosis is still elusive in breast cancer. Our study showed that CLDN6 was associated with ferroptosis in breast cancer patients. The integration of CLDN6 and ferroptosis demonstrated remarkable predictive prognostic performance. We observed that CLDN6 triggers NRF2-mediated ferroptosis in vitro and in vivo. Mechanistically, CLDN6 enhanced nuclear export of NRF2 by regulating the PBK-dependent AKT/GSK3β/FYN axis. Further CLDN6 recruited PBK to the cell membrane through the endosomal pathway and bound with the DLG1/PBK complex, thereby promoted the degradation of PBK by the UPS. This study elucidates the previously unrecognized mechanism of CLDN6 triggering NRF2-mediated ferroptosis through recruiting DLG1/PBK complex. This study provides a reliable biomarker for predicting prognosis and is anticipated to guide the selection of therapies targeting ferroptosis in breast cancer.